Central control of cardiorespiratory interactions in fish - Taylor, Edwin W.; Leite, Cleo A. C.; Levings, Jennifer J. (Elsevier Gmbh, Urban & Fischer Verlag, 2009)
Fish control the relative flow rates of water and blood over the gills in order to optimise respiratory gas exchange. As both flows are markedly pulsatile, close beat-to-beat relationships can be predicted. Cardiorespiratory interactions in fish are controlled primarily by activity in the parasympathetic nervous system that has its origin in cardiac vagal. preganglionic neurons. Recordings of efferent activity in the cardiac vagus include units firing in respiration-related bursts. Bursts of electrical stimuli delivered peripherally to the cardiac vagus or centrally to respiratory branches of cranial, nerves can recruit the heart over a range of frequencies. So, phasic, efferent activity in cardiac vagi, that in the intact fish are respiration-related, can cause heart rate to be modulated by the respiratory rhythm. In elasmobranch fishes this phasic activity seems to arise primarily from central feed-forward interactions with respiratory motor neurones that have overlapping distributions with cardiac neurons in the brainstem. In teleost fish, they arise from increased levels of efferent vagal activity arising from reflex stimulation of chemoreceptors and mechanoreceptors in the orobranchial, cavity. However, these differences are largely a matter of emphasis as both groups show elements of feed-forward and feed-back control of cardiorespiratory interactions. (C) 2008 Elsevier GmbH. All rights reserved.
Keywords: Review; Fish; Cardiorespiratory interactions; Heart; Autonomic control; Vagus